Internet of Things with Raspberry Pi 3 : Leverage the power of Raspberry Pi 3 and JavaScript to build exciting IoT projects. - Rao, Maneesh (Packt Publishing, 2018)
Internet of Things (IoT) is currently a growing trend in the technology space, and Raspberry Pi is the perfect board to get started with building IoT projects. Applications of IoT are the basis of smart homes and when scaled up, we can drive smart cities and achieve manufacturing automation. This book covers many powerful features of ...